Rise husk derived bioactive glass-ceramic and its polymeric composite scaffolds for cancellous bone regeneration - Farnaz Naghizadeh, 1980-, author; Mohammed Rafiq Abdul Kadir, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2015)
Thesis (Ph.D (Kejuruteraan Bioperubatan)) - Universiti Teknologi Malaysia, 2015